Assiduous Folklore Worker - Kadžytė, Gražina (Tautosakos darbai, 2019)
In 2019, the 100th anniversary of the famous Lithuanian folklorist Ambraziejus Jonynas (1919–2006) is celebrated. This publication gives a detailed survey of his biography, scholarly works and public activities. The main research interests of Jonynas comprised the folklore historiography. Besides, he edited or co-authored a number of the most important collective theoretical works by the Lithuanian folklorists and folklore publications printed in the second half of the 20th century.
Keywords: -